Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/ruq.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Shear Wave Elastography Findings and Histologic Prognostic Factors of Invasive Breast Cancer

Abstract: Objective Shear wave elastography (SWE) is an adjunct to grayscale ultrasound examinations for evaluating breast masses. This study aimed to determine the SWE features that correlated with prognostic parameters for breast cancer. Methods Between January 2018 and May 2018, 80 patients who were confirmed to have invasive cancers by core-needle biopsy and who were scheduled for surgery were imaged using B-mode ultrasound and SWE. Measurements were taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Although the presence of cluster, coarse or large calcifications in benign breast masses can induce apparent high stiffness in benign lesions resulting in the misdiagnosis of malignancy (Gregory et al 2015), no statistically significant relationship between the elasticity of invasive masses and the presence of calcifications was found in our study. This is in agreement with the study reported in Gemici et al (2020). Interestingly, f mass was found to be significantly correlated with the presence of calcifications.…”
Section: Discussionsupporting
confidence: 93%
“…Although the presence of cluster, coarse or large calcifications in benign breast masses can induce apparent high stiffness in benign lesions resulting in the misdiagnosis of malignancy (Gregory et al 2015), no statistically significant relationship between the elasticity of invasive masses and the presence of calcifications was found in our study. This is in agreement with the study reported in Gemici et al (2020). Interestingly, f mass was found to be significantly correlated with the presence of calcifications.…”
Section: Discussionsupporting
confidence: 93%
“…However, they showed no significant correlation between PR, ER, HER-2, or Ki-67 proliferation index and SWE stiffness rates. Similarly, other studies have shown a significant correlation between lymph node metastasis, histologic grade, lymphovascular invasion, and sonoelastographic results, but different results for immunohistochemical parameters and sonoelastography have been obtained 12,22,23 .…”
Section: Discussionmentioning
confidence: 79%
“…Gemici et al showed no correlation between the elastography values obtained using SWE and immunohistochemical parameters or molecular subtyping 22 . In the same study, it was shown that there were significant correlations between SWE stiffness rates and lymphovascular invasion, lymph node metastasis, and histological grade.…”
Section: Discussionmentioning
confidence: 99%
“…However, in real scenarios, these medical data differ to some extent in terms of light intensity, viewpoint, background, etc. Meanwhile, the quality of medical image annotation relies on the degree of expertise of the annotators, which requires years of accumulated expertise and experience [20]. Provide information, including tumor size, shape, edge, echo pattern, whether there is attenuation behind, and whether there is calcification inside, etc., to provide a basis for finding breast cancer.…”
Section: Discriminatory Analysis Of Abnormal Data From Glandular Imagesmentioning
confidence: 99%